Bridging the gap between understanding and action: A participatory study on watershed conservation - Zulham, Moh. Dian; Rahman, Abdul; Pribadi, Hendra; Maiwa, Arman; Alam, Andi Sahri; Massiri, Sudirman Daeng (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Watershed conservation in Poboya Village, Mantikulore District is very important to maintain ecosystem balance and environmental sustainability, considering that the river plays a role as the main source of water for downstream areas. This study aims to find out the role of the community in watershed conservation in Poboya Village, Mantikulore District. Method: This research was carried out in Poboya Village, Mantikulore District for 1 month, from April to May 2025. The sampling technique used was snowball sampling. The data collection of this research was carried out through the distribution of questionnaires with a Likert scale, conducting in-depth interviews, and using an open-ended approach. Findings: The results of the research obtained from 30 respondents in Poboya Village, Mantikulore District, found that the level of public understanding of watershed conservation is classified as high, with an average score of 116. This shows that the community in general has a good understanding of the concept, function, and importance of watershed conservation, including the influence of natural factors and human activities on the condition of watershed ecosystems. The role of the community in watershed conservation efforts is also categorized as moderate, with an average score of 86. Less active communities participate in various conservation activities such as planting trees on riverbanks, domestic waste management, the use of conservative agricultural techniques, and involvement in environmental outreach and campaigns. Conclusion: The community in Poboya Village shows a strong understanding of watershed conservation but demonstrates moderate levels of participation in related activities. There is a need to enhance community involvement in practical conservation efforts through increased education, outreach, and empowerment initiatives. Novelty/Originality of this Article: This study contributes to the understanding of community-based watershed conservation by highlighting the disparity between awareness and active participation, specifically in a local village context where water resources are directly linked to the livelihoods of downstream populations.